2020
DOI: 10.1021/acsami.0c13540
|View full text |Cite
|
Sign up to set email alerts
|

High Spin to Charge Conversion Efficiency in Electron Beam-Evaporated Topological Insulator Bi2Se3

Abstract: Bi 2 Se 3 is a well-established topological insulator (TI) having spin momentum locked Dirac surface states at room temperature and predicted to exhibit high spin to charge conversion efficiency (SCCE) for spintronics applications. The SCCE in TIs is characterized by an inverse Edelstein effect length (λ IREE ). We report an λ IREE of ∼0.36 nm, which is the highest ever observed in Bi 2 Se 3 . Here, we performed spin pumping and inverse spin Hall effect (ISHE) in an electron beam-evaporated Bi 2 Se 3 / CoFeB b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…This work demonstrates promising results for gate‐controlled spin polarization and suggests a novel method for measuring spin polarization in a TI quantitatively. The research group has shown the thickness dependence of spin pumping and spin Hall effect in TI channel at room temperature, [ 49 ] which suggests the possible application to electronic devices. In principle, our method is valid at room temperature and therefore our work should be useful for characterizing new spintronic materials and developing spintronic devices.…”
Section: Discussionmentioning
confidence: 99%
“…This work demonstrates promising results for gate‐controlled spin polarization and suggests a novel method for measuring spin polarization in a TI quantitatively. The research group has shown the thickness dependence of spin pumping and spin Hall effect in TI channel at room temperature, [ 49 ] which suggests the possible application to electronic devices. In principle, our method is valid at room temperature and therefore our work should be useful for characterizing new spintronic materials and developing spintronic devices.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the set-up can also be found elsewhere. 10,[13][14][15][16][17][18][19][20] 3 Results and discussion Resonance field (H res ) and linewidth (DH) are evaluated from the ferromagnetic resonance spectra. The FMR data (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…ISHE measurements have been performed by connecting a nanovoltmeter over two ends of the sample (sample size: 3 mm × 2 mm). The details of the ISHE set-up can be found elsewhere [11,12,[23][24][25][26][27][28].…”
Section: Methodsmentioning
confidence: 99%